Venture philanthropy waqf model: a conceptual study - Azliza Azrah Mohd Zakaria,; Rose Ruziana Abd. Samad,; Zurina Shafii, (Penerbit Universiti Kebangsaan Malaysia, 2013)
The concept of venture philanthropy has been greatly discussed by various parties especially among the policy makers. The increasing social problems call for corporations to respond positively and take responsibilities in the social sector. It encourages venture philanthropy activities among profit and non-profit organizations in enhancing business values and creating positive social impacts. There have been past studies that looked at how venture philanthropy concept can be linked with Islamic philanthropy. Islamic philanthropy includes but not limited to zakat, waqf and sadaqah. The instruments within Islamic philanthropy aim to serve the purpose of narrowing social distance and reducing inequalities. This conceptual paper aims to understand further the concept of venture philanthropy and how it links to Islamic philanthropy. This paper also aims to explore how venture philanthropy approach is applicable in enhancing waqf practices.